PEMANFAATAN INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PEMASARAN PARIWISATA DI KABUPATEN CIAMIS (STUDI KASUS INSTAGRAM @DISPARCIAMIS) - Putri, Shafira Eka; Dharmawan, Leonard (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
This study investigates the effectiveness of Instagram as a digital communication medium in enhancing the image and attractiveness of tourism destinations. The research is motivated by the question of how the Instagram-based promotional strategy implemented by @disparciamis supports tourism promotion in Ciamis Regency and which types of content most effectively capture tourist interest. The study aims to analyze the effectiveness of digital communication strategies within the framework of integrated marketing communication, as well as to identify dominant and contextually relevant content for target audiences. A descriptive qualitative approach was employed, consisting of systematic observation of Instagram posts, in-depth interviews with the Head of the Marketing Division and members of the media team of the Ciamis Regency Tourism Office, along with supporting documentation. The findings indicate that @disparciamis applies a strategic combination of visual content development, digital interaction, brand identity consistency, and cross-sector collaboration, all of which align with the core principles of integrated marketing communication. Informative visual content—particularly photographs, short videos, and educational narratives—emerges as the most engaging form for attracting tourists. Overall, the study concludes that Instagram plays a crucial and sustainable role in shaping a positive tourism image for Ciamis Regency, serving not only as a promotional tool but also as a platform for fostering audience engagement and strengthening destination branding.